Church communication in the face of vulnerability: a theoretical framework and practical application for information management in cases of the abuse of minors - Carroggio, Marco (Church, Communication and Culture, 2021)
This article is mainly aimed toward those responsible for communications in ecclesial organizations that are experiencing vulnerability. It integrates the perspective of organizational communication with ecclesiological contributions. The first part notes that vulnerability is a common trait of civil and ecclesial organizations, both in the passive sense (potential to be hurt) and in the active sense (capacity to do harm). In the second part, a circular conceptual framework of the process of communication, devised by several academics from the Pontifical University of the Holy Cross, is developed and applied to the Church. In pursuing adherence to reality, this is a valid theoretical framework for inspiring the communication management that is required for dealing with errors and failures. In the description of the process, references are added to the issue of fragility in each of its phases: identity, culture, discourse, image, and reputation. A key word in this sequence is ‘consistency’ (between what an institution is, and how it considers itself; what it does, and what it says). In the third part, this ‘realistic’ conceptual universe is applied to the issue of the abuse of minors committed by ministers of the Catholic Church, guidelines for the communications team are suggested (investigate, listen, accompany, repair), and seven criteria for proper reporting are proposed.